Tomato Fruit Polygalacturonase Isozyme 1 (Characterization of the [beta] Subunit and Its State of Assembly in Vivo). - Moore, T. (1994)
Polygalacturonase isozyme 1 (PG1) is a heterodimer comprising a catalytic and noncatalytic or [beta] subunit, whereas polygalacturonase isozyme 2 (PG2) comprises only the catalytic subunit. To assess the state of assembly of PG1 in vivo, both subunits were purified to homogeneity and used to study assembly of the heterodimer. PG1 could be reconstituted in vitro from purified [beta] subunit and purified PG2 under a wide range of salt and pH conditions, and PG1 reconstituted in vitro was indistinguishable from PG1 isolated from tomato (Lycopersicon esculentum) fruit. Specific antibodies indicated that the [beta] subunit was present in fruit of all developmental stages, but absent in vegetative tissue. The state of assembly of PG1 in vivo was tested based on the differential thermal stability of PG1 and PG2 by heating segments of ripe fruit pericarp tissue. Temperatures well below those required to inactivate PG1 in vitro caused the loss of activity of both PG1 and PG2, suggesting that only heat-labile PG2 is present in vivo. In addition, when extracts of ripe fruit were rigorously maintained and analyzed at 4[deg]C, PG1 was absent or barely detectable. These results are consistent with the hypothesis that PG1 can assemble spontaneously and is essentially absent in intact tomato fruit but forms artifactually from PG2 and the [beta] subunit during the extraction of tomato fruit tissue when low temperatures are not rigorously maintained.